Perioperative Analgesic Efficiency of Ultrasound-Guided Quadratus Lumborum Block versus Epidural Analgesia in Bladder Cancer Patients Undergoing Radical Cystectomy - Bakeer, Ahmed; Abdelhamid, Khaled; Nabil, Dina; Rawi, Mohamed (Open Access Macedonian Journal of Medical Sciences, 2022)
Background and Aim: Multimodal analgesia is currently used for perioperative pain management after Radical cystectomy (RC). This study aimed to compare quadratus lumborum block (QLB) and thoracic epidural block (TEA) in patients subjected to RC. Methods: This prospective randomized controlled study included 34 patients with bladder cancer subjected to RC under general anesthesia, divided into two groups. The Quadratus Group (n=17) underwent bilateral ultrasound-guided continuous QLB, and the Epidural Group (n=17) underwent continuous TEA. The primary outcome was pain intensity measured by VAS score, and the secondary outcomes were total morphine consumption during the first 48 hours after surgery, postoperative nausea score, and patient satisfaction. Results: There were no differences between the two groups in postoperative VAS scores starting immediately after surgery up to 48 hours. Reduction of VAS score after QLB was delayed compared to that after TEA. The two groups had a comparable number of patients requesting rescue analgesia (p = 0.271) and total postoperative morphine consumption (p = 0.976) in the remaining patients. The nausea score was significantly lower in the Quadratus Group than in the Epidural Group (p = 0.020). There was no significant difference between the two groups in the satisfaction score (p=0.612). Few mild complications were detected in the two studied groups. Conclusion: QLB and TEA are safe and effective in managing postoperative pain after radical cystectomy with similar analgesic profiles. QLB was more effective in reducing postoperative nausea and vomiting.